OPTIMIZING RPG PATHFINDING A HYBRID APPROACH FOR STATIC AND DYNAMIC OBSTACLE AVOIDANCE - Gunawan, Renaldy Ari; Istiono, Wirawan (Bakti Nusantara Institute, 2023)
Playing a role The popular game genre known as